The Role of Teacher Working Groups in Supporting the Implementation of the Independent Curriculum in Teacher Professional Development - Pramesti Arumingtyas; Kartika Chrysti Suryandari; Winarno Winarno (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Teaching skills are one of the focuses of teacher professional development in order to support the implementation of the Independent Curriculum. The objectives of this study are: 1) To describe the implementation of the independent curriculum in elementary schools, 2) To describe the efforts of the Teacher Working Group in supporting the implementation of the Independent Curriculum, 3) To describe the factors that influence the effectiveness of teacher professional training and development. This research method is descriptive qualitative. The research sample consisted of 59 teachers in elementary schools. Data collection methods were carried out through in-depth interviews, observation, and documentation. Data validity used data triangulation, method triangulation, and theory triangulation. Furthermore, the data were analyzed using the Miles and Huberman model with data reduction, data presentation, and drawing conclusions. The results of the study show: 1) The active involvement of teachers in the Teacher Working Group has a significant impact on improving the understanding of the Independent Curriculum concept and teaching skills in accordance with the curriculum. 2) Training combined with technical guidance and collaborative discussions accelerates teacher competency improvement in implementing the Independent Curriculum. 3) There are challenges related to the limitations of the training methods used, so diversification of training methods is needed to be more interactive and practice-based. These findings confirm that teacher working groups as a forum for developing teacher professionalism can create a positive collaborative atmosphere to support the implementation of the Independent Curriculum in elementary schools.